P316 Influence of transcranial direct current stimulation on electrophysiological and behavioral correlates of cognitive fatigue in multiple sclerosis. Issue 3 (March 2017) - Fiene, M.; Heinze, H.-J.; Vielhaber, S.; Zaehle, T.
Abstract : Introduction: Cognitive fatigue is one of the most common and difficult to treat symptoms affecting patients with Multiple Sclerosis (MS). Previous studies suggested structural and functional abnormalities in the frontal cortex, especially a frontal hypo-activation, as a possible substrate for fatigue. Fatigue severity can be quantified by prolonged reaction times (RT) in alertness tests accompanied by lower amplitudes of the P300 event-related potential. Objectives: In the present study we investigated whether neuromodulation of the left dorsolateral prefrontal cortex (DLPFC) by means of transcranial direct current stimulation (tDCS) has influence on electrophysiological and behavioral correlates of cognitive fatigue in MS. Materials and Methods: 15 MS patients with cognitive fatigue symptoms were enrolled in the study. In two sessions they were either stimulated with anodal tDCS (1.5 mA, 25 min) or sham stimulation over the left DLPFC. To assess fatigue severity, P300 during an auditory oddball task and performance on a simple reaction time test were recorded at baseline, during and after stimulation. Results: Analysis revealed a significant stimulation effect on the P300 component. Compared to baseline, anodal but not sham tDCS caused an increase in P300 amplitude that persisted after the end of stimulation. In addition, anodal tDCS significantly attenuated the fatigue-related increase in RT over the course of a testing session. Conclusion: Our findings demonstrate that a single dose of anodal tDCS over the left DLPFC has positive effects on electrophysiological and behavioral correlates of cognitive fatigue. In accordance with previous studies that showed a subjective fatigue relief by repeated stimulation sessions, our findings give important insight into the potential underlying mode of action of tDCS. The results provide causal evidence for a functional relevance of the left DLPFC in the pathogenesis of cognitive fatigue and show that tDCS-induced modulations of frontal activity can be a promising therapeutic option for the treatment of MS-related fatigue.